Pengembangan Model Latihan Sepak Bola Melalui Pendekatan Holisitik - Zulmi, Reli Afri (Jurnal MensSana, 2023)
The problem of this research is that there is no soccer training model that combines elements of physical, mental, technical and tactical training or a holistic training model in West Sumatra. The aim of this research is to create a holistic soccer training model. Research Design is research development from Borg & Gall. The research subjects were SSB Alam Sakti U-14 soccer athletes and three soccer experts as assessors. Development of training models by testing the model with small and large group tests with test and retest, expert validity using a questionnaire instrument and testing the reliability of the tool with correlational r. The results of the expert assessment were 93%, 87% and 89% respectively in the "proper" category. The small group agility test results obtained a mean of 12.98 s standard deviation 1.8489 for the large group mean 13.14 s standard deviation of 2.1165 "had an increase". The stages of developing a holistic training model are looking for potential problems, data collection, product design, design validation, design revision, product trial, product revision, usage trial, and product revision, expert validation test obtained validity of 89.6% "Very Good" and reliability test small group 0.999 "High" and large group 0.997 "High".